The specificity of the provisions of the criminal liability of the legal person in business crimes - Saadi, Abdelhalim (Journal of Human Sciences, 2022)
If the Principle admitted into criminal legislation. that the criminal responsibility is personal and is attributed only to the author on the one hand, and is only attributed to the natural person who is considered to be the source of the criminal responsibility, but the tremendous development of the rules of criminal liability due to being affected by several factors, have required the monitoring of all persons and actions and activities that have contributed to the occurrence of the crime within the framework of companies and economic institutions. This necessitated the expansion of the scope of criminal liability in business crimes to the legal person due to the specificity and gravity of these crimes on the national economy, and the legislator distinguished them with rules and special procedures.